Is there a Role for Genetic Counselors in Prenatal Paternity Testing? – an Assessment Based on Audit of 13 years of Clinical Experience in South Australia. Issue 1 (21st July 2016) - Riley, Kate E.; Salvemini, Hayley; Haan, Eric; Fitzgerald, Lara; Stallard, Kirsty; Borrie, Sarah; Pontikinas, Electra; Baxendale, Anne
Abstract: The role of genetic counselors in prenatal paternity testing has not been widely studied in the genetic counseling literature. In South Australia, the genetic counselors of the State's public sector clinical genetics service are the primary contact point for women seeking information and testing, also coordinating the testing process. This has provided the opportunity to review all prenatal paternity testing performed in the State over a 13 year period and to consider the role played by the genetic counselor. We explored the reasons why women requested prenatal paternity testing and whether the genetic counselor was an appropriate health professional to facilitate this testing for women. The study had two parts, an audit of the clinical genetics files of 160 women who requested prenatal paternity testing between March 2001 and March 2014, and qualitative interviews of genetic counselors, clinical geneticists, obstetricians and social workers with involvement in this area. The audit determined that in 69.9 % of cases the long‐term partner was the father of the pregnancy, for 23.7 % the short‐term or other partner was the father and for 6.4 % the paternity results were not known by the genetic counselor. For 45.5 % of women whose long‐term partner was excluded as the father, the women chose to have a termination of pregnancy. The results of the qualitative interviews yielded five major themes: accessibility of testing, role of the genetic counselor, social and relationship issues, decision making in pregnancy and emotional issues. We conclude that the genetic counselor is an appropriate health professional to facilitate prenatal paternity testing. Genetic counselors did not view their role as significantly different from a request for prenatal testing for another indication.